Dinamika Komunitas Generasi Radar Banten dalam Menulis Berita dan Artikel - Muhammad Umar Atala; Yuniati Yuniati; Adhi Kusuma (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Journalistic communities play a strategic role in shaping young journalists, one of which is Generasi Radar Banten. This study aims to analyze the dynamics of the Generasi Radar Banten community in guiding its members in writing news and articles, identify the training methods used, and examine the challenges faced in the journalistic learning process. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observations, and document analysis related to the community’s activities. The findings reveal that the community has a structured mentoring system through workshops, discussions, and field practice in news coverage and writing. The applied learning methods adhere to journalistic principles such as the inverted pyramid, feature writing, and editing techniques. Challenges encountered include limited resources, varying skill levels among members, and adaptation to digital media changes. Nevertheless, the community has successfully enhanced members' writing skills and expanded their professional networks. In conclusion, Generasi Radar Banten plays a significant role in training young journalists by providing effective learning programs. This study recommends strengthening the mentoring system and adapting to media technology developments to improve the quality of learning in journalistic communities.